Encounter and React: Computer-Guided Design of Covalent Inhibitors. Issue 1 (17th January 2019) - Ung, Peter Man-Un; DeVita, Robert J.; Schlessinger, Avner
Abstract : Covalent inhibitors can obtain optimal selectivity and extended residence time. In this issue of Cell Chemical Biology, Shraga et al. (2019) take a comprehensive computational and experimental approach to modulate the JNK-Jun pathway through design of MKK7 covalent inhibitors. This study highlights a promising and emerging strategy for therapeutic discovery. Abstract : Covalent inhibitors can obtain optimal selectivity and extended residence time. In this issue of Cell Chemical Biology, Shraga et al. (2019) take a comprehensive computational and experimental approach to modulate the JNK-Jun pathway through design of MKK7 covalent inhibitors. This study highlights a promising and emerging strategy for therapeutic discovery.